8(3x-6)=6(4x+8)

Simple and best practice solution for 8(3x-6)=6(4x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3x-6)=6(4x+8) equation:


Simplifying
8(3x + -6) = 6(4x + 8)

Reorder the terms:
8(-6 + 3x) = 6(4x + 8)
(-6 * 8 + 3x * 8) = 6(4x + 8)
(-48 + 24x) = 6(4x + 8)

Reorder the terms:
-48 + 24x = 6(8 + 4x)
-48 + 24x = (8 * 6 + 4x * 6)
-48 + 24x = (48 + 24x)

Add '-24x' to each side of the equation.
-48 + 24x + -24x = 48 + 24x + -24x

Combine like terms: 24x + -24x = 0
-48 + 0 = 48 + 24x + -24x
-48 = 48 + 24x + -24x

Combine like terms: 24x + -24x = 0
-48 = 48 + 0
-48 = 48

Solving
-48 = 48

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 58.7=x | | 4-(2x+5)=-3x+1 | | 13v=-195 | | -2=m/3-4 | | -11=5n+6n | | (3x-1)+31+x=180 | | X=6+0.75x | | -6-4(-7x-13)=58 | | -12+2x+x-8=10 | | 2(w-3)-6=-4w+3(w-5) | | 0=0.5*(x-0.5+0.5x-0.33) | | 9(x+4)=-27 | | 12-0.75(x+15)=4 | | f/3=2 | | x/2-10=0 | | 16=2s+-40 | | y=45x+160 | | 7+6g=25 | | X=.75x+6 | | 51=-9d-8d | | 2*22/7*50 | | 405=15b | | -2y+40=8y | | 2x22/7x50 | | -9+5x=7x-5 | | 14-6p=-16 | | 6(12+x)=360 | | n/3-6=1 | | 2(5x-3)=44 | | 3(n-7)-(4-2n)=4n | | 5y+-17=58 | | 6a+4c=238 |

Equations solver categories